Memory’s ransom: silences, postmemory, cinema (Abril – NEPA / UFF, 2021)
Close to half a century after their end, the colonial wars Portugal waged in a desperate and doomed attempt to hold on to its African colonies in 1974 remain still largely unprocessed. This article examines the multiple silences surrounding the colonial wars and the 25th April Revolution in Portugal drawing from the concept of postmemory and the notion of a traumatic past whose wounds have never healed. It argues that silence in the end does nothing more than allow those open wounds to go on festering. The combined silence over the dictatorship and the colonial wars was never more than a mild palliative, yet another self-delusion the nation allowed itself as it attempted to put on its new European costume. The article focuses on two films, Inês de Medeiros’ Cartas a uma Ditadura (2006) and Ivo M. Ferreira’s Cartas da Guerra (2016), their differences and their similarities, singling out the work of postmemory evident in the scenes with Belmira Monteiro and her granddaughter in the former.------------------------------------------------------------O RESGATE DA MEMÓRIA: SILÊNCIOS, PÓS-MEMÓRIA, CINEMAPassados quase cinquenta anos depois do seu fim em 1974, as guerras coloniais que Portugal travou em África numa tentativa desesperada e condenada ao fracasso de assegurar o domínio das suas colónias, continuam ainda por processar devidamente. Este artigo examina os silêncios múltiplos ao redor das guerras coloniais e da Revolução de 25 de Abril em Portugal a partir do conceito de pós-memória e da noção de um passado traumático cujas chagas nunca sararam. Avança a sugestão de o silêncio manter essas feridas em aberto. O silêncio combinado que recaiu sobre a ditadura e as guerras coloniais nunca foi mais que um paliativo suave, mais uma das ilusões que a nação se permitiu para melhor vestir o seu novo traje Europeu. Este artigo debruça-se sobre dois filmes, Inês de Medeiros’ Cartas a uma Ditadura (2006) e Ivo M. Ferreira’s Cartas da Guerra (2016), as suas diferenças e semelhanças, salientando o trabalho de pós-memória evidente nas cenas do primeiro em que Belmira Monteiro figura com a sua neta.---Original em inglês.